As origens da concepção de história de Karl Marx: da crítica de Kreuznach aos manuscritos de Paris - Toledo, Iago Augusto Martinez de (2022)
The purpose of this dissertation is to investigate the origins of Karl Marx's conception of history. In order to do so, we resort to the immanent analysis of a set of texts written by Marx between 1843 and 1844, which shape the Marxian production from the Kreuznach critique – through the letters and texts published in the Franco-German yearbooks – to the Paris Manuscripts. In this brief period of fertile intellectual production and intense practical-theoretical reorientation, one can see the parallel between the formation of Marx's political-philosophical thought and the formation of his conception of history. The genesis and development of the Marxian conception of history are shaped through ontological critiques of philosophical speculation, politicity (in particular, political emancipation) and classical political economy. Each of these critiques reveals both a moment in the development of the Marxian conception of history and reveals the tendencies towards it and the component elements of its general and universalizing structure. In this way, we can also see the parallelism between the formation of Marx's ontological position – which establishes the general physiognomy of his prima philosophia – and the formation of his conception of history. This highlights the impossibility of disaggregating history and ontology in Marxian thought in general. At the end, it is seen how the Marxian conception of history is a historical-ontological conception of the development of the social being. In it, history shines forth as the fundamental determinant of all human-societal form and content, and is conceived as the concrete-contradictory making of the become-permanently-social of individuals according to the concrete imperatives of historical circumstances